PERBANDINGAN SISTEM HUKUM PEMBUKTIAN DALAM PENANGANAN PERKARA TINDAK KORUPSI DENGAN PERKARA TINDAK PIDANA LAINNYA - Fira Mubayyinah (LPPM Institut Agama Islam Al-Hikmah Tuban, 2017)
Proof is one of a series conducted in the court process to seek the truth, proving a guideline in ways that justified the law remedy prove whether the defendant's right or wrong, Proof is also a provision governing evidence which justified the law and may be used to prove mistakes indicted judges (M. Yahya Harahap) KUHAP we have set in Article 183